Desertificação na região dos Inhamuns: uma análise a partir de indicadores de pressão-estado-resposta - Caetano, Francisco Aquiles de Oliveira (2022)
In the state of Ceará, there are three desertification Nuclei or Desertification Areas - NDA, located on the “Sertões de Irauçuba and Centro-Norte”, “Sertões dos Inhamuns” and “Sertões do Médio Jaguaribe”. These areas are the focus of strategies aimed to revert this phenomenon, with one of the most relevant being the elaboration of the State Action Program to Combat Desertification and Mitigation of the Effects of Drought - PAE-CE. Therefore, the objective of this study is to characterize desertification in the Inhamuns region. Primary data obtained through the application of forms, occurred in January 2018, with leaders of rural communities located in the Municipalities of Arneiroz, Independencia and Tauá, inserted in the NDA, was used. As methodological procedures, the PER (Pressure - State - Response) methodology was initially adopted to describe the situation of desertification in the region, with the support of several indicators. The main results showed that state indicators are the most determining factors in desertification in the region. It was detected that most communities are in an intermediate level of desertification.